INGRESO POR SERVICIO DE LA EMPRESA MULTIALFA S.A. DE LA CIUDAD DE GUAYAQUIL - CEDEÑO VILLAVA, KATTY VERONICA (2018)
he satisfaction of the clients is one of the main objectives of the company to be able to maintain and retain them and with this achieve greater productivity, a factor that the organization promotes to be able to stay in the market. The service company Multialfa S.A. of the city of Guayaquil was created on June 25, 2003, it is located in the cooperative El Ceibal Mz. 2245S. 30. Has 7 employees, the owner is Mr. Rubén López and the administrator Ms. Tatiana López. It has three departments: administration, sales and services.